A New Taxon of Basal Ceratopsian from China and the Early Evolution of Ceratopsia - Han, Fenglu; Forster, Catherine A.; Clark, James M.; Xu, Xing (PLOS ONE, 2015)
Ceratopsia is one of the best studied herbivorous ornithischian clades, but the early evolution of Ceratopsia, including the placement of Psittacosaurus, is still controversial and unclear. Here, we report a second basal ceratopsian, Hualianceratops wucaiwanensis gen. et sp. nov., from the Upper Jurassic (Oxfordian) Shishugou Formation of the Junggar Basin, northwestern China. This new taxon is characterized by a prominent caudodorsal process on the subtemporal ramus of the jugal, a robust quadrate with an expansive quadratojugal facet, a prominent notch near the ventral region of the quadrate, a deep and short dentary, and strongly rugose texturing on the lateral surface of the dentary. Hualianceratops shares several derived characters with both Psittacosaurus and the basal ceratopsians Yinlong, Chaoyangsaurus, and Xuanhuaceratops. A new comprehensive phylogeny of ceratopsians weakly supports both Yinlong and Hualianceratops as chaoyangsaurids (along with Chaoyangsaurus and Xuanhuaceratops), as well as the monophyly of Chaoyangosauridae + Psittacosaurus. This analysis also weakly supports the novel hypothesis that Chaoyangsauridae + Psittacosaurus is the sister group to the rest of Neoceratopsia, suggesting a basal split between these clades before the Late Jurassic. This phylogeny and the earliest Late Jurassic age of Yinlong and Hualianceratops imply that at least five ceratopsian lineages (Yinlong, Hualianceratops, Chaoyangsaurus + Xuanhuaceratops, Psittacosaurus, Neoceratopsia) were present at the beginning of the Late Jurassic.